(untitled) (UNIZIK Journal of Marketing, 2025)
This study adopted the mixed methods comprising the qualitative and quantitative content analyses. Using both primary and secondary data, it combined oral interviews and thematic preoccupation approaches to analyse the application of information asymmetry in relation to the Nigerian business environment. The research was anchored on the frameworks of information asymmetry and trade puffery. Information asymmetry deals with information imbalance between the seller and the buyer while the trade puffery concerns itself with unsubstantiated exaggerations and claims about a product or service. The coding was both thematic and quantitative. The former enabled the researchers to identify, analyse and freely interpret the patterns of meaning within the qualitative data. In the quantitative coding buyer response was represented on tables with simple percentages. Despite its complexities, the holistic population of study enhanced accurate representation thereby reducing bias risks. It also enabled the researchers to engage in a comprehensive and multifaceted study of the sellers and buyers. The sample size was the 100 respondents drawn through convenience sampling, a non-probability and quick technique, was used to select respondents based on their ease of access and availability. The simple random sampling was finally used to select respondents for oral interviews. Findings revealed the factors promoting information asymmetry in the Nigerian market situations, exposed buyer opinion and ugly experience in the hands of dubious sellers. Finally, it investigated the legal provisions and court litigations against dishonest sellers, as well as the solution.